2008
DOI: 10.1108/03090560810877123
|View full text |Cite
|
Sign up to set email alerts
|

A strategic marketing intelligence and multi‐organisational resilience framework

Abstract: PurposeThe paper seeks to explain how competitive intelligence officers can participate more fully in strategy formulation and implementation, and how they can contribute to the strategic intelligence process.Design/methodology/approachThe paper presents a review of the literature and the development of a strategic marketing intelligence and multi‐organisational resilience framework.FindingsCompetitive intelligence officers can contribute more fully to the strategic intelligence process and help establish an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 37 publications
(38 reference statements)
2
45
0
Order By: Relevance
“…The conceptual framework for studying change in SMEs is shown in Figure 1. This view of change management, whilst being consistent with Pettigrew et al's (1992) 'context-processcontent' view for studying change, also incorporates the key concepts raised in the organisational resilience literature such as building flexible plans, vision setting, readiness for change, communication, proactive approach to change, empowering employees, creating a culture of change and managing resistance to change (Hamel and Valikangas 2003, Bolton 2004, Seville et al 2006, Tompkins 2007, Alesi 2008, Trim and Lee 2008. 5606 A. Ates and U. Bititci…”
Section: A Conceptual Change Process For Building Resilient Smesmentioning
confidence: 79%
See 2 more Smart Citations
“…The conceptual framework for studying change in SMEs is shown in Figure 1. This view of change management, whilst being consistent with Pettigrew et al's (1992) 'context-processcontent' view for studying change, also incorporates the key concepts raised in the organisational resilience literature such as building flexible plans, vision setting, readiness for change, communication, proactive approach to change, empowering employees, creating a culture of change and managing resistance to change (Hamel and Valikangas 2003, Bolton 2004, Seville et al 2006, Tompkins 2007, Alesi 2008, Trim and Lee 2008. 5606 A. Ates and U. Bititci…”
Section: A Conceptual Change Process For Building Resilient Smesmentioning
confidence: 79%
“…Organisations with a clear long-term plan that are well understood and communicated find it easier to approach a crisis situation to stay stable and resilient (Seville et al 2006). By adopting a proactive approach through well-thought plans, SMEs can become more resilient and this is underpinned by the firm's vision, value system and leadership (Tompkins 2007, Trim andLee 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines on how MI systems should be developed have been formulated (Goretsky, 1983), and possible designs for such systems have been proposed (King & Cleland, 1974;Rothschild, 1979;Montgomery & Weinberg, 1998;Mockler, 1992;Trim, 2004). Other authors have suggested that information specialists could participate more in the strategic decision-making process and have outlined conceptual processes for doing so (Trim & Lee, 2008). Yet, despite the importance attached to MI and other marketing information functions, surprisingly few studies have explicitly examined the relationship between MI and strategic marketing decisionmaking, a gap in the extant literature this article addresses.…”
Section: Introductionmentioning
confidence: 99%
“…Because these are the main arguments that consist the basis of MSI. According to this, in narrow sense, the competitive intelligence is described as "the informatics that provide businesses to be the more effective", however, this definition is not thought enough, the definition made by Business Intelligence Institute in America is assessed as the most adequate one (Trim and Lee, 2008;Trim, 2004;Walle, 1999a;1999b;Powell and Allgaier, 1998).…”
Section: The Concept Of Strategic Marketing Intelligencementioning
confidence: 99%